Synthesis of TiO2 by Hydrolysis/Electrochemical to Reduce Hazardous Disinfecting Materials - Adrian Nur; Arif Jumari; Nazriati Nazriati; Fauziatul Fajaroh (Program studi Teknik Kimia UNS, 2017)
The TiO2 photo-catalysis can be used for the purpose of disinfectant purpose. In this work, the TiO2 prepared by hydrolysis-electrochemical method was used to produce disinfectant to replace and reduse conventional material disinfectant. The synthesis of TiO2 was occured at constant voltage of 10 V for 2.5 hours under constant stirring and room temperature. The product of synthesis was analysed by scanning electron microscopy, energy dispersive X-ray spectrometry, and X-ray diffractometer. The performance of desinfectant was done with inactivation of bacteria E coli in solid media. The phase of TiO2 particle producted shows anatase and rutile phase. The TiO2 resulted from hydrolysis/electrohemical method can be used to reduce HCl for desinfectant. The results of testing disinfectant for inactivation of bacteria E coli in solid media show that disinfectant from HCl/TiO2 is the most efective to inactivation of bateria E. coli. Treatment with ultraviolet rays resulted less number of bacteria than sunlight.